PERFORMANCE OF WHEAT (Triticum aestivum L.) GENOTYPES UNDER SALT STRESS CONDITIONS - Rahaman, F.; Chowdhury, A. K.; Bashar, H. M. Khairul; Uddin, M. S. (Bangladesh Journal of Plant Breeding and Genetics, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><span style="font-size: 10.0pt; mso-bidi-font-size: 14.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Studying genetic variability for abiotic stresses like salt is important for crop improvement. To identify the genotypic diversity of wheat for salt tolerance, this study was carried out at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute, Rahmatpur, Barisal in 2007-2008 using 12 genotypes under five different salinity levels (e.g. 4, 8, 12, 16 dS/m) and control. Plant morphological and yield contributing traits showed a range of variability. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Genotypic variabilities were more prominent in plant height, number of spikes plant-1, number of grains plant-1, 100-grain weight and grain yield plant-1. <span style="font-size: 10.0pt; mso-bidi-font-size: 14.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Genotype <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">G40 ranked top for most of the yield related<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> traits followed by G33. While, G24 outperformed over all the genotypes for 100-grain weight and grain yield per plant.<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> There was no effect of heading on salinity though other plant characters were affected by increasing level of salinity. Considering the responses of plant characters to salinity G40, G33 and G24 were found to be more salt tolerant than others. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">These three genotypes can therefore be useful for further genetic and physiological study. DOI: http://dx.doi.org/10.3329/bjpbg.v25i2.18661